Curriculum Management in the Intercultural School - Pratami, Andhyarnita; Sugiarto, Sugiarto; Ahmad, Masduki (International Journal of Elementary Education, 2021)
Curriculum management is one of the important components in the process of providing education in an educational unit. Therefore, curriculum management should receive more attention as an effort to optimize the quality of education. This study aims to analyze curriculum management in intercultural schools. The focus of this research is the component of curriculum management which consists of the curriculum planning stage, the organizing stage, the implementation stage, and the evaluation stage. This research is research using a qualitative descriptive approach. The data in this study were collected through observation and interviews with principals, teachers, and representatives of curriculum developers. The data that has been collected is then analyzed using the data analysis method according to Milles and Huberman which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that curriculum management/management in intercultural schools has been implemented by following the stages of curriculum development which include planning, organizing/coordinating, implementing, and evaluating curriculum stages. The implementation of the stages of curriculum development shows that the curriculum management process has been carried out in a good category.